Oral microbiota in patients with oropharyngeal cancer with an emphasis on Candida spp. - N. S. Bagirova; I. N. Petukhova; Z. V. Grigorievskaya; A. V. Sytov; P. V. Slukin; E. A. Goremykina; O. E. Khokhlova; N. K. Fursova; A. E. Kazimov (Опухоли головы и шеи)
Introduction. Interactions between the 2 microbiota components – bacteria and fungi – are of interest as diagnostic and prognostic markers in selection of treatment tactics for oncological patients.Aim. To study microbiota of the oral cavity in patients with primary squamous cell carcinoma of the oropharyngeal area before and after surgical intervention to find biomarkers for rational selection of antifungal drugs.Materials and methods. At the Surgical Department of Head and Neck Tumors of the N. N. Blokhin National Research Center of Oncology, three-component study was performed: investigations of spectrum of Candida spp. isolates, Candida spp. strains’ resistance to antifungals, and oral washes in primary patients before and after surgery. mALDI-Tof microflex LT (Biotyper, Bruker Daltonics, germany) was used for strain identification; Sensititre Yeast ONE, YO10 (Trek Diagnostic System, united kingdom) plates were used for determination of minimal inhibiting concentrations of anti fungals. values of minimal inhibiting concentrations were evaluated based on the European Committee on Antimicrobial Susceptibility Testing (EuCAST) criteria (version 10.0).Results. four-year observation of patients at the surgical department of head and neck tumors of the N. N. Blokhin National Research Center of Oncology showed that the most common species of Candida is C. albicans (73.5 % of cases). Candida spp. resistance to antifungals was detected only for fluconazole (9.3 % of cases) and micafungin (8.0 % of cases), mostly among C. albicans strains. In 31.8 % of primary patients, oral washes prior to surgery showed growth of Candida spp. (probably, tissue colonization). After surgical intervention, Candida spp. growth was detected in 36.4 % of cases, only 1 of which was diagnosed as invasive mycosis. In 54.5 % of cases before and in 72.7 % of cases after surgery, gram-negative rods were detected. After surgical intervention, percentage of enterobacteria and non-fermenters significantly increased: 59.1 % versus 27.3 % (p <0.05) and 63.6 % versus 27.3 % (p <0.02), respectively. prior to surgery, non-fermenting gram-negative bacteria were represented only by P. aeruginosa; after surgery, the spectrum of non-fermenting gram-negative bacteria became wider but percentage of P. aeruginosa remained high: 71.4 %. ERG11 gene was identified only in 1 strain: C. albicans. FKS1 gene also was identified only in 1 strain: C. inconspicua. virulence factor genes were detected in 57.1 % of strains.Conclusion. Surgical intervention is associated with changes in bacterial microbiota but not fugal microbiota. presence of virulence factor genes and resistance genes in Candida spp. strains should be considered a biomarker allowing to differentiate between colonization and candida infection and can be used for rational selection of antifungal drugs in prevention and treatment of invasive candidiasis, especially in the absence of criteria for interpretation of measured minimal inhibiting concentrations of antifungals.